Estudo do Conceito de Taxa de Variação: Análise de Coleções de Livros Didáticos do Ensino Médio - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The study Calculation of Higher Education requires students, changes in relation to the study in basic education, in particular as regards the development of abstract deductive thought in basic education is usually not shown, which can contribute to high rates of failures. Whereas the student of higher education in general needs to understand the concepts related to the Rate of Change and this is working in Basic Education, the objective of this research was to analyze the textbooks of high school three schools of an inside county state of Rio Grande do Sul, in order to check how it is being presented the concept of rate of change in specific topics functions under the transitional perspective of elementary mathematical thinking to advanced. The choice of subject was due, as mentioned, the importance of understanding the concept of rate of change in high school and the implications of this concept in higher education. For this, it sought theoretical foundation in the theory of Advanced Mathematical Thinking (PMA), problematized by authors Tall (1991) Dreyfus (1991) and Gray (1999). It was adopted as a working methodology to qualitative research and document analysis of Bardin (1977). Analysis of the data provided a better understanding of how the concept of rate of change is addressed in the works of high school and has highlighted the presence of some WFP processes in the proposed activities, as well as space and time dedicated to the concept.
Keywords: Taxa de Variação.; Pensamento Matemático Avançado.; Análise de livros didáticos.; Rate of change.; Advanced Mathematical Thinking.; Textbooks Analysis.; CNPQ::CIENCIAS EXATAS E DA TERRA